Implementation of Learning Assessment in State Islamic Elementary Schools of Rejang Lebong Regency - Fhina Devira Fhina; Firda Syifa Azizah; Amalya Putri; Siti Zulaiha; Tika Meldina (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
The implementation of formative and summative assessments in the Merdeka Curriculum had been finished using technology from grades I to VI in State Islamic Elementary Schools (MIN) of Rejang Lebong Regency. The implementation of these assessments has included problems, such as obstacles that were experienced by teachers. Therefore, this study has two objectives: 1) determine the implementation of assessments at State Islamic Elementary Schools (MIN) in Rejang Lebong Regency. 2) Determine the problems experienced by teachers in implementing assessments at State Islamic Elementary Schools (MIN) in Rejang Lebong Regency. This study used a qualitative method by using a descriptive research design. The data sources obtained were primary and secondary data. This study used data collection techniques such interviews and documentation. Data collection was carried out through in-depth interviews to the school principals, teachers, and students. The data analysis techniques used consist of data reduction, data display, and conclusion drawing. The results of the study demonstrated that 1) the implementation of assessments at State Islamic Elementary Schools (MIN) in Rejang Lebong Regency has been implemented according to the regulation, both in the learning process and in the duration laid out in the curriculum, and have applied technology such as Google Forms, Microsoft Forms, and Quizizz, especially in the higher grades, such as grades 4, 5, and 6. 2) There are several problems in the implementation of both formative and summative assessments, related to the use of technology in assessments conducted by teachers, such as limited time, differences in student abilities, insufficient facilities and infrastructure, unstable internet connections, limitations in student devices, and the use of personal data plans.